Short Selling and Its Regulation in Indonesia: Debating Ownership through Fiqh Muamalah - Kukuh Prasetyo Idzharul Haq; Ahmad Solahuddin (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2026)
Short selling has gained formal regulatory recognition in Indonesia through POJK No. 6 of 2024, yet its position remains contested in the Islamic capital market. The central problem lies in whether securities may be sold before they enter the seller’s lawful ownership and possession. Using a normative juridical approach, this paper examines DSN-MUI Fatwa No. 40/2003, Fatwa No. 80/2011, Fatwa No. 135/2020, POJK No. 6 of 2024, and relevant fiqh muʿāmalah literature on mulk, qabḍ, bayʿ al-maʿdūm, gharar, maysir, and ribā. The analysis shows that POJK No. 6 of 2024 regulates short selling through authorization, securities lending, collateral, reporting duties, order marking, and market supervision. These mechanisms may reduce operational risk and support market governance, but they do not remove the Sharia ownership problem. DSN-MUI Fatwa No. 80/2011 prohibits short selling because the seller sells securities not yet owned at the time of transaction. Fatwa No. 135/2020 strengthens this reasoning by defining shares as ownership participation. Regulatory recognition, therefore, does not automatically create Sharia legitimacy. Short selling remains difficult to justify in Indonesia’s Islamic capital market unless ownership, possession, fair risk bearing, and lawful entitlement are preserved. Short selling memperoleh pengakuan regulatif di Indonesia melalui POJK No. 6 Tahun 2024, tetapi praktik tersebut tetap menimbulkan persoalan dalam perspektif pasar modal syariah. Permasalahan utamanya berkaitan dengan keabsahan penjualan efek sebelum berada dalam kepemilikan dan penguasaan sah pihak penjual menurut prinsip syariah. Penelitian ini menggunakan pendekatan yuridis normatif dengan menelaah Fatwa DSN-MUI No. 40/2003, Fatwa DSN-MUI No. 80/2011, Fatwa DSN-MUI No. 135/2020, POJK No. 6 Tahun 2024, serta berbagai literatur fiqh muʿāmalah mengenai konsep mulk, qabḍ, bayʿ al-maʿdūm, gharar, maysir, dan ribā. Hasil penelitian menunjukkan bahwa POJK No. 6 Tahun 2024 mengatur short selling melalui mekanisme perizinan, securities lending, penyediaan agunan, pelaporan transaksi, penandaan order, serta pengawasan pasar untuk menjaga stabilitas dan transparansi perdagangan efek. Meskipun mekanisme tersebut mampu mengurangi risiko operasional dan memperkuat tata kelola pasar modal, pengaturan tersebut belum menyelesaikan persoalan mendasar mengenai kepemilikan dalam hukum syariah. Fatwa DSN-MUI No. 80/2011 secara tegas melarang short selling karena penjual menjual efek yang belum dimiliki saat akad berlangsung. Larangan tersebut diperkuat oleh Fatwa DSN-MUI No. 135/2020 yang menempatkan saham sebagai bukti partisipasi kepemilikan. Dengan demikian, pengakuan regulatif tidak otomatis melahirkan legitimasi syariah terhadap praktik short selling